PEWARISAN HARTA DI MINANGKABAU DALAM PERSPEKTIF KOMPILASI HUKUM ISLAM - Rika Febri Anti Lubis; Rabiatul Abawiyah (Al Qadhi, 2023)
Inheritance of inheritance in Minangkabau is viewed from the collection of Islamic law. The results of this research show that there are several similarities and differences between the Minangkabau Traditional Heritage Book and the Islamic Law Book. The similarity lies in the concept of inheritance of inferior inheritance, and in the Islamic legal system, inferior inheritance is included in inheritance because it is included in milk al-raqabah. The next similarity is inheritance with collective institutions. This is found in Articles 183 and 189 of the Compilation of Islamic Law. Finally, there is the issue of subsidies. is a subsidy that is included in Minangkabau customs. is actually a subsidy. Subsidies are included in Islamic law (fiqh). However, the difference with , the inheritance is large. Large inherited assets cannot be classified as inherited assets. From this we can conclude that the Minangkabau Customary Number wealth inheritance system is in accordance with Islamic law.